Kyai Leadership in Efforts to Increase the Independence of Student - Chusnul Chotimah; sahrul saputra (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
This research discusses the role of kyai leadership in increasing the independence of students at the Bahrul Ulum Islamic Boarding School (parents) Tambakberas Jombang. The research method used is descriptive qualitative through observation, interviews and documentation at the Islamic boarding school. The conclusion of the research shows that KH. Fatkhullah Malik, MPd., as a kyai at the Bahrul Ulum Islamic Boarding School, implements democratic leadership by accepting input from his subordinates. This approach relies on good moral and ethical principles to achieve common goals. Factors supporting student independence involve emotional, economic and intellectual aspects. Emotional independence is built through a positive teaching system, economic independence is strengthened by adequate facilities, and intellectual independence is enhanced through active participation in the teaching and learning process. However, there are also three factors inhibiting students' independence, including emotional dependence and low self-confidence, lack of economic skills and limited access to economic resources, as well as lack of motivation to learn and inability to adapt to the curriculum. Thus, this research illustrates the importance of kyai leadership in forming santri independence by emphasizing supporting factors and overcoming obstacles that may arise in the process.